(untitled) (Marketing Journal, 2026)
This article analyzes the role and importance of the KPI (Key Performance Indicators) system in improving the effectiveness of personnel management in the activities of commercial banks. The study examines modern approaches to human resource management in the banking system, existing problems in evaluating employee performance, and the possibilities of addressing these issues through the implementation of the KPI system. Using the example of a credit manager in a commercial bank, a KPI -based performance eva luation model is developed, and its practical application is demonstrated.